National Libraries' Traditional Collection Policy Facing Web Archiving. Issue 3 (December 2013) - Shveiky, Rivka; Bar-Ilan, Judit
One of the main missions of a national library is to preserve the national creative works in printed and non-printed formats. In the 1990s, national libraries began to harvest and archive the national body of creative work that was published on the internet. The aim of the study was to examine to what extent national libraries implement their general collection policy when they establish a national web archive. The study, which was based on a qualitative approach, had three phases: examining the characteristics of a traditional collection policy of a national library; identifying the characteristics of a collection policy of a national library's web archive; and comparing the traditional collection characteristics with the national library's web archive characteristics. The results showed that although the libraries that were studied were from different regions of the world and various cultures, the characteristics of their traditional collections are similar. In contrast, the difference between their web archives is more significant. National libraries do not apply the traditional policy to the internet, and struggle to shape new rules for coping with web contents.